Internal Reporting Guidelines: Their Coverage in Cost Accounting Texts. - Hardy, John W.; Hubbard, E. Dee (The Accounting Review, 1976)
Abstract This article presents and interprets findings of a study in which several current textbooks in cost and managerial accounting were examined to determine the extent of reference to and coverage of the reporting guidelines accepted as given. It is suggested that accountants should be concerned about effectiveness of internal and external accounting reporting. In the said study, researchers have accepted as given several guidelines relating to effective internal reporting systems; these were assembled from an examination of the current literature in the fields of organizational behavior and communication. The guidelines that were identified are classified into two groups: preparation and reporting or feedback. According to preparation guidelines: objectives should reflect goal congruence; participants should help set goals and agree to selected measures of goal achievement; standards should be set with freedom for failure and changes; accountants should educate report recipients; and accountants should recognize the tendency to over- or underestimate plans. According to reporting guidelines: reports should be relevant to user needs and responsibilities; reports should be on a personal level; reports should include supportive comments; reports should be consistent; and that reports should be timely and regular.